2013
DOI: 10.1155/2013/892746
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Water Parameters on Monthly Seagrass Percentage Cover in Lawas, East Malaysia

Abstract: Seagrass is a valuable marine ecosystem engineer. However, seagrass population is declining worldwide. The lack of seagrass research in Malaysia raises questions about the status of seagrasses in the country. The seagrasses in Lawas, which is part of the coral-mangrove-seagrass complex, have never been studied in detail. In this study, we examine whether monthly changes of seagrass population in Lawas occurred. Data on estimates of seagrass percentage cover and water physicochemical parameters (pH, turbidity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Declines were associated with storm and cyclone activity and similar to other nearby seagrass areas and natural disturbances such as weather changes affect seagrass populations (Ahmad-Kamil et al, 2013;Mckenna et al, 2015) and productivity were expected to decrease with decreasing water clarity (van Tussenbroek et al, 2014). Our research found that a combination of these factors has resulted in significant damage to hundreds of meters of seagrass beds (Orth et al, 2006;Short et al, 2006;Brigitta et al, 2014).…”
Section: Introductionsupporting
confidence: 64%
“…Declines were associated with storm and cyclone activity and similar to other nearby seagrass areas and natural disturbances such as weather changes affect seagrass populations (Ahmad-Kamil et al, 2013;Mckenna et al, 2015) and productivity were expected to decrease with decreasing water clarity (van Tussenbroek et al, 2014). Our research found that a combination of these factors has resulted in significant damage to hundreds of meters of seagrass beds (Orth et al, 2006;Short et al, 2006;Brigitta et al, 2014).…”
Section: Introductionsupporting
confidence: 64%
“…Both Weston and Menumbok estuaries are formed by Sungai Padas and Sungai Klias, respectively, and run in a north-east direction. The mangrove vegetation, together with seagrass beds and coral reefs in Brunei Bay, are providing several eco-socio-economic benefits to the local communities ( Ahmad-Kamil et al, 2013 ). This study was conducted with the permission of the State Forestry Department of Sarawak (# NCCD.907.4.4 (Jld.…”
Section: Methodsmentioning
confidence: 99%
“…The coastal and marine ecosystems in this bay comprise mangrove forests, seagrass beds, estuarine systems, mudflats and coral reefs (Bali 2005, Bujang et al 2006. Also, this bay has a continental slope (Ahmad-Kamil et al 2013), where the continental shelf is 50-70 km wide and underlained by 8-10 km of siliciclastic sediments (Straub et al 2012). At a sea depth of ~200 m the continental shelf-slope break occurs, and the seabed descends steeply to reach the floor of the Borneo Trough at a sea depth of 2800 m (Straub and Mohrig 2009).…”
Section: Study Areamentioning
confidence: 99%